The unicity and the diversity: Factors at issue - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
It is assumed that the unicity and the diversity of clinics are present in its protagonists: the patient (or healthy person) and the clinical doctor; in their patient-doctor relationship (or healthy-doctor); in the clinical method, as a concrete expression of the scientific method applied to the individual care of a person and in the daily processes in which all these relationships and persons are involved: medical care, teaching, research and management. It is emphasized in the value of a debate about clinics, as the base of medical care of an individual person, could report new concepts and approaches that could benefit first, to the patients that are cared.